Pelatihan Penggunaan Mmicrosoft Office Bagi Guru SMP Al-Hamidiyah Palembang - Masayu Rosyidah; Marhaini Marhaini; Reny Kartika Sary; Febi Ardianto; Yosi Apriani (UII, 2019)
The teacher is a professional educator with the task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early and secondary education in certain formal institutions. One of the problems faced by Al-Hamidiyah Middle School teachers is the low competency of teachers, especially in the use of computer technology devices. This is unfortunate, even though the demands on teachers' assignments are in line with the enactment of the 2013 curriculum, where teachers are required to work using applications, learning media using information technology, application-based assessment systems, computer-based national exams, and others. This obstacle occurs because there is still a lack of teacher motivation to add competence outside the main task for a variety of reasons conveyed. The approach used in this dedication activity with a persuasive-educative approach, by providing knowledge, understanding, and skills in using Microsoft Office. The method used in the form of lectures, practice, and discussion. The results of this dedication the teacher understands and is able to practice directly.